Success Treatment of Severe and Active Graves' Orbitopathy with Tocilizumab After Thyroidectomy and Maximum Dose of Intravenous Methylprednisolone - Laurentius Aswin Pramono (Interna Publishing, 2023)
We report a woman, 45th year old with Graves' disease treated with anti-thyroid drug (thiamazole). She came to our clinic with severe and active Graves' orbitopathy. We treated her with high dose intravenous methylprednisolone weekly (0.5 g weekly/ 6 weeks) and mycophenolate sodium 0.72 g daily/ 6 weeks. Because of her longterm consumption but not successful to achieve remission of anti-thyroid drugs and the size of her goiter, we decided to do total thyroidectomy. Only one week after thyroidectomy, her eye inflammation grade was reduced, but still bulging. We continue with the intravenous methylprednisolone weekly. Because of the partial response, we continue with another dose of methylprednisolone (0.25 g weekly for another 6 weeks). After 12 weeks of intravenous methylprednisolone (maximum dose for 1st course 4.5 g), there is a partial response make it to moderate to severe grade but still active inflammation. Our team decided to give her second-line treatment and we give her intravenous tocilizumab monthly for 4 weeks. After three tocilizumab infusion, the inflammation is reduced remarkably. Her overall appearance is getting better. But, because of her sight was not improved much as the inflammation reduced, we done orbital MRI and we decided to do another intravenous methylprednisolone 1 g for three days followed by orbital decompresion surgery. Shortly after the orbital decompresion, her sight was improved very well. She can now doing activities she can do previously. After recovery, we plan to give her the fourth (last) tocilizumab infusion. Overall, tocilizumab improves clinical outcome in patient with active corticosteroid-resistant moderate to severe Graves' orbitopathy. Patient's quality of life also improved.